PENGARUH WAKTU PENCUCIAN TERHADAP SIFAT MEKANIS PRODUK LATEKS KARET ALAM RENDAH PROTEIN - - Yuniati; - Adriana; Ramzi Jalal (Politeknik Negeri Lhokseumawe, 2014)
This study is aimed to observe the use of coconut shell used as Carbon for filler material for gloves making. Two important factors in making gloves with the immersion technique are leaching and heating processes that can increase the mechanical properties. This research is also aimed to find a solution of washing procedure and the best time to get the mechanical properties, so the laundering can reduce the allergic reaction for the sentive users... A method which has been experienced is maturation process for 24 hours and was condunted of vulcanization by drying it in the oven with 100 °C for 15 minutes. The leaching process of the film is conducted by using some sort of solutions ; aquadest, 1% sodium hydroxide and 1% Ammonium hydroxide . The examining time used for laundering and soaking are 30, 60 and 90 minutes.. The highest tensile strength was obtained in 30 minutes soaking time with 25,3 MPa Aquadest. . The tensile strength increased along with the extra time for laudering and soaking process in 90 minutes with aqudest and 90 minutes with 800 % sodium hydroxide. . The highest modulus , 300 %, was obtained in 90 minutes soaking/ laundering time in 1,7 Mpa Ammonium Hydroxide solution